Roman Medan: The Nature and Socio-political Context of a Corpus in Sumatran Popular Literature 1930s-1960s: (Roman Medan: Dunia dan Konteks Sosiopolitik sebuah Korpus Sastera Popular di Sumatera, 1930an-1960an) (Malay Literature, 2019)
Roman Medan is the name given to one of the major corpuses of Indonesian popular literature that was mostly published in Medan, the most important city in the northern part of Sumatra, since the 1930s onwards-the final decades of the colonial era. The corpus survived for about decades before disappearing in the late 1960s. Another term given to these works was roman Sumatera (Sumatran novels), while the Dutch scholar R. Roolvink called them dubbeltjes-roman (roman pitjisan in Indonesian, literally meaning "dime novel"), which reflects a rather disparaging attitude. This article explores the nature, socio-political and historical contexts of roman Medan, especially relating to the cultural politics in Indonesia towards the end of the Dutch colonial period. In this way, it is hoped that readers will get a clear picture of the position of the corpus, textually and sociologically, in the history of modern Indonesian literature.Keywords: roman Medan, roman Sumatera, roman pitjisan, popular literature, literary history, cultural politics, colonialism, Dutch East Indies, modern Indonesian literature